Real estate market analysis : trends, methods and information sources - Brett, D.L
Summary: The industry-standard introductory guide on analyzing real estate markets, this edition includes comprehensive updates on previous editions while providing a practical "how-to" for evaluating several property types. In addition to highlighting development trends and explaining recognized research and analysis methods, this third edition provides an updated and expanded list of information sources, both national and local, for a wide range of property types. -- Adapted from back cover